2020
DOI: 10.31557/apjcp.2020.21.4.1103
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Double Expresser in Selected Cases of High Grade Diffuse Large B-Cell Lymphomas

Abstract: Human Immunodeficiency Virus (HIV), Epstein Barr Virus (EBV), Hepatitis C Virus (HCV), Human T Leukemia Virus (HTLV), exposure to certain chemicals including pesticides, hair coloring agents, and herbicides e.g 2,4-dichlorophenoxyacetic acid (2,4-D) (Chiu and Blair, 2009). There are two main categories of lymphomas: Hodgkin (HL) and Non-Hodgkin lymphoma (NHL). Hodgkin lymphoma has been further divided into five subtypes on the basis of types of cells and their morphological arrangements (Alizadeh et al., 2000)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This last approach is very controversial since DLBCL constitutes a great number of non-Hodgkin lymphomas, accounting for 30-40% of all B-cell lymphomas in western countries, thus encompassing high financial costs 23 . This is particularly evident if we consider the low frequency of these chromosomal anomalies since, for instance, DH-HGBL has been reported as accounting for around 4% of DLBCL cases 22 .…”
Section: Discussionmentioning
confidence: 99%
“…This last approach is very controversial since DLBCL constitutes a great number of non-Hodgkin lymphomas, accounting for 30-40% of all B-cell lymphomas in western countries, thus encompassing high financial costs 23 . This is particularly evident if we consider the low frequency of these chromosomal anomalies since, for instance, DH-HGBL has been reported as accounting for around 4% of DLBCL cases 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The reported frequency is 1.5-4.3% in previously reported studies [ 14 - 16 ]. However, to date, very limited data are available at the international level regarding cyclin D1 expression in triple-hit lymphoma to label it as quadruple-hit lymphoma [ 6 ]. In this study, the frequency of cyclin D1 expression was studied, and it was found that in double expressors, the frequency of cyclin D1 is 5%.…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan, exact statistics regarding the incidence of HGBL are unknown, as there is no cancer registry at the national level. According to one study conducted in Pakistan [ 6 ], the frequency of double-expressers is 14%. However, no data are available regarding the frequency of triple expressors in our population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nagib et al studied double-expressor DLBCL and found that it was associated with an overall decreased disease-free survival [ 8 ]. Naseem et al studied the frequency and prognosis of double-expressor DLBCL and found that the frequency of c-MYC/BCL-2 co-expression was 14%, with a median survival of 10 months [ 9 ]. Conversely, we found a higher frequency of double-expressor phenotype in our study (35.8%).…”
Section: Discussionmentioning
confidence: 99%